A clinical approach to hypertrophic pachymeningitis - Fabiano Ferreira Abrantes; Marianna Pinheiro Moraes de Moraes; Flávio Moura Rezende Filho; José Luiz Pedroso; Orlando Graziani Povoas Barsottini (Arquivos de Neuro-Psiquiatria)
ABSTRACT Importance: Hypertrophic pachymeningitis (HP) is a non-usual manifestation of rheumatologic, infectious, and neoplastic diseases. Etiological diagnosis is a challenge, but when made promptly it creates a window of opportunity for treatment, with the possibility of a total reversal of symptoms. Observations: HP is an inflammatory process of the dura mater that can occur as a manifestation of sarcoidosis, granulomatosis with polyangiitis, and IgG4-related disease. The HP case evaluation is extensive and includes central nervous system imaging, cerebrospinal fluid analysis, serology, rheumatologic tests, and systemic survey for other manifestations sites. After systemic investigation, meningeal biopsy might be necessary. Etiology guides HP treatment, and autoimmune disorders are treated with corticosteroids alone or associated with an immunosuppressor. Conclusion: HP is a manifestation of several diseases, and a precise etiological diagnosis is crucial because of the difference among treatments. An extensive investigation of patients with HP helps early diagnosis and correct treatment.